2007
DOI: 10.1590/s1676-26492007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Níveis cardíacos de troponina I em pacientes com epilepsia do lobo temporal refratária após cortico-amígdalo-hipocampectomia

Abstract: OBJETIVOS: A morte súbita em epilepsia (SUDEP) é a principal causa de morte entre os pacientes com epilepsia. Alterações morfológicas e funcionais do coração estão relacionadas com a SUDEP. Nesse sentido, o objetivo deste estudo foi avaliar a concentração de troponina I, um importante marcador de lesão do miocárdio, em pacientes com epilepsia do lobo temporal de difícil controle e que foram submetidos à ressecção cirúrgica e que não obtiveram sucesso com esta abordagem terapêutica. METODOLOGIA: Onze pacientes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Colugnati DB et al reported an increase in CTnI level in nearly 30% and 83.3% of patients with uncomplicated and complicated epilepsy, respectively (17). In addition, in a study by Chaiworapongsa et al, the level of CTnI increased marginally in newborns of preeclamptic mothers; this finding was attributed to a mild myocardial damage (18).…”
Section: Discussionmentioning
confidence: 96%
“…Colugnati DB et al reported an increase in CTnI level in nearly 30% and 83.3% of patients with uncomplicated and complicated epilepsy, respectively (17). In addition, in a study by Chaiworapongsa et al, the level of CTnI increased marginally in newborns of preeclamptic mothers; this finding was attributed to a mild myocardial damage (18).…”
Section: Discussionmentioning
confidence: 96%